Development of electronic atlas based on identification of herbaceous vegetation in mount mutis national park - Djalo, Aloysius; Missa, Hildegardis; Ndukang, Sardina; Baunsele, Anselmus Boy; Nau, Getrudis W.; Sepe, Florentina Y. (JURNAL BIOEDUKATIKA, 2025)
Gunung Mutis National Park (TNGM), located in South Central Timor Regency, East Nusa Tenggara, contains a diverse range of highland herbaceous vegetation with the potential to be used as a learning resource. However, the lack of locally contextualized learning media poses challenges for Biology Education students in identifying herbaceous species during field studies. This research aims to develop an electronic atlas (e-atlas) based on herbaceous vegetation identification in TNGM as an interactive digital learning medium. This study employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), involving 25 students and 3 expert validators. Data were collected through validation questionnaires, learning outcome tests, student questionnaires, and lecturer reflections, then analyzed using descriptive quantitative methods. The results indicate that the e-atlas is valid in terms of content and design, practical in application, visually engaging, and effective in enhancing students' understanding of herbaceous species. A total of 12 species from 8 families were documented and included in the e-atlas, complete with scientific information. This e-atlas has the potential to serve as a contextual learning medium based on local resources, promoting ecological literacy and improving botany education in conservation areas.